Sustainable Intensification vs. Farms` Economic Outcomes – the case of Poland - Wrzaszcz, Wioletta (European Journal of Sustainable Development, 2017)
The concept of agriculture intensification, in traditional terms, is understood as a process of increasing inputs of work units and/or industrial means of production in order to increase production per unit of agricultural land or animal. Having regard to the greater human pressure to natural environment, there is the need of sustainable intensification implementation. Sustainable intensification concerns agricultural productivity increase, simultaneously reducing agriculture negative impact on ecosystem. Sustainable intensification can be understood in two different ways. The first one refers to inputs minimization, mainly industrial inputs, although such practices may result in reduction of economic outcomes. The second approach is based on the use of agrobiological processes in factor productivity improvement. In this case, of particular importance is the farmer`s extensive knowledge, which translates to the quality of agri-environmental practices, as well as the use of environmentally friendly traditional and modern production technologies. The purpose of the article is economic assessment of farms in Poland, diversified in the scope of sustainable intensification process. This process was evaluated on the basis of soil fertility data, namely balance of soil organic matter. Farm Accountancy Data Network was used (2004, 2015). Keywords: sustainable intensification, soil fertility, soil organic matter balance, economic outcomes, farms sustainability, Farm Accountancy Data Network, Poland